IL FALCO PELLEGRINO (Falco peregrinus) IN SICILIA - Sara' M; Mascara R; Zanca L (Edizioni Belvedere, 2021)
having doubled in number during the period 1978-2006, the population of the Peregrine Falcon Falco peregrinus living in Sicily currently seems to be stable, and has very probably reached the carrying capacity at the current ecological conditions of the insular ecosystems. A continuous standardized census (2010-2019) estimated at least 257 pairs scattered across the main island, plus some 13-15 pairs living on the small islands around Sicily. The population is not randomly distributed, but rather it is concentrated in all the suitable habitats of the island, nesting in either small crags or large cliffs from sea level to 1,424 m asl; it is rarer in the north-eastern corner (Peloritani, Nebrodi, Aetna), with their mainly densely forested areas, and with fewer cliffs. In these less suitable parts of the region the density is half (0.5 vs 1 pair/100 km2) and the Nearest Neighbour Distance is double (10.7 vs 5.2 km) than the rest of the island. The reproduction cycle was delayed by 9 days (median values: from 28 February to 9 March) in the last 50 years, due to higher spring precipitations that negatively affected productivity. Currently (2010-2019), only 72% of pairs reproduce successfully, with an average fledging rate of 2.49±0.77 juveniles. Young peregrines disperse inside the island with occasional trips to the small islands nearby. Biologging and genetic data would suggest a relatively closed population. Illegal shooting, poisoning, electrocution and collision with wind towers and electroducts are the main causes of unnatural mortality. Annually a small quota of nests is still being robbed.